Punishment and Welfare: Paternal Incarceration and Families’ Receipt of Public Assistance - Naomi F. Sugie
The US criminal justice and welfare systems together form important government interventions into the lives of the poor. This paper considers how imprisonment is related to welfare receipt for offenders and their families. Using longitudinal data from the Fragile Families and Child Wellbeing study, it investigates how recent paternal incarceration is associated with families' receipt of TANF, food stamps, and Medicaid/SCHIP. Results robust to multiple tests find that incarceration does not increase the likelihood of TANF receipt but significantly increases food stamps and Medicaid/SCHIP receipt. Further, the effect of incarceration on welfare receipt is larger than the recent loss of father's employment. The findings suggest that an unexpected consequence of mass imprisonment is the expansion of government regulation through welfare provision for offender's families.Fragile Families and Child Wellbeing study, imprisonment, welfare, criminal justice, welfare system, food stamps, Medicaid/SCHIP, incarceration